A flexible response of NATO to potential threats occurring on the eastern border - Robert Czerski; Marek Kustra; Krzysztof Goniewicz (Kazimierz Wielki University, 2019)
From the beginning of The North Atlantic Pact has been based on the concept of collective defense. This assumption takes on meaning after 2014. The annexation of Crimea to Russia and the hybrid war in Ukraine are confirming the Increase of military threat to the NATO border states, Including Poland. None of the eastern flank countries it would be able to oppose Russian aggression themselves. The Decisions are Strengthen the eastern flank are going to Effectively deterring threats from military escalation. This action take place thanks to the presence of international contingents.